2018
DOI: 10.1155/2018/3927096
|View full text |Cite
|
Sign up to set email alerts
|

Shaofu Zhuyu Decoction Regresses Endometriotic Lesions in a Rat Model

Abstract: The current therapies for endometriosis are restricted by various side effects and treatment outcome has been less than satisfactory. Shaofu Zhuyu Decoction (SZD), a classic traditional Chinese medicinal (TCM) prescription for dysmenorrhea, has been widely used in clinical practice by TCM doctors to relieve symptoms of endometriosis. The present study aimed to investigate the effects of SZD on a rat model of endometriosis. Forty-eight female Sprague-Dawley rats with regular estrous cycles went through autotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…However, according to the warning from the Herbal Pharmacopeia [ 39 ], leonuri Herba (Yi Mu Cao) and Shao-Fu-Zhu-Yu-Tang should be used with caution during pregnancy due to possible adverse effects such as increased contractile frequency and activity of the uterus [ 40 ]. We speculate that these herbs are likely to be used by older, highly educated women to treat infertility caused by dysmenorrhea and endometriosis disease [ 41 , 42 ]. Therefore, we recommend that TCM physicians should be cautious when prescribing CHM for pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the warning from the Herbal Pharmacopeia [ 39 ], leonuri Herba (Yi Mu Cao) and Shao-Fu-Zhu-Yu-Tang should be used with caution during pregnancy due to possible adverse effects such as increased contractile frequency and activity of the uterus [ 40 ]. We speculate that these herbs are likely to be used by older, highly educated women to treat infertility caused by dysmenorrhea and endometriosis disease [ 41 , 42 ]. Therefore, we recommend that TCM physicians should be cautious when prescribing CHM for pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Pentobarbital sodium and rabbit polyclonal antibody against cyclooxygenase-2 (ab15191; Abcam, UK) were purchased from Beijing Diweile Biotechnology Co., Ltd. e SFZYD contained 11 herbs: Foeniculi Fructus, Zingiberis Rhizoma, Corydalis Rhizoma, Myrrha, Rhizoma, Angelica Sinensis Radix, Radix Paeoniae Rubra, Cortex Cinnamomi, Typhae Pollen, and Trogopteri Feces. e origins, medicinal parts, and weight ratios of these herbs have been described in a previous article [18]. We created the formulation as follows.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…SFZYD is now widely used in TCM therapy for endometriosis. Our previous study showed that SFZYD inhibited cellular proliferation, promoted apoptosis, and reduced angiogenesis in ectopic endometrial tissues, thus playing a role in the treatment of endometriosis [ 18 ]. The purpose of the present study is to investigate our hypothesis that letrozole and SFZYD act on gut microbiota to inhibit the progression of lesions in rats with EMs.…”
Section: Introductionmentioning
confidence: 99%
“…Shaofu Zhuyu Decoction (SZD) consists of ten commonly used herbs and has been widely used in clinical practice to relieve symptoms of endometriosis. SZD significantly reduced the size of ectopic lesions inhibited cell proliferation, increased cell apoptosis, and reduced MVD, HIF-1 α and CD34 expression in the ectopic endometrium in a rat model [ 159 ].…”
Section: Resultsmentioning
confidence: 99%